Redefinition of the genus Argonychiurus Bagnall, 1949 (Collembola, Onychiuridae) with description of a new species from Georgia - Djanashvili, Revaz; Barjadze, Shalva; Jordana, Rafael; Burkhardt, Ulrich (Zootaxa, 2014)
The genus Argonychiurus was established by Bagnall (1949) based on the type species Onychiurus perforatus Handschin, 1920. He included Onychiurus bertrandi Denis, 1936 in this newly erected genus, together with O. perforatus.